Secuenciación genómica y análisis del genotipo argentino de soja convencional "INTA-FICA 5C k/lx [Glycine max (L.) Merr ] - Fumero, María Verónica; Bernardi, Clarisa Noelia; Garis, Sol Belén; Lenzi, Lisandro German; Amadio, Ariel; Irazoqui, Jose Matias; Cappuccio, Javier Alejandro; Soldini, Diego Omar; Vanzetti, Leonardo Sebastian (Centro Regional Córdoba, INTA, 2023)
Poster